USAGE RATE OF THE UNLICENSED MEDICATIONS IN NEONATOLOGY: DATA OF THE PHARMACO EPIDEMIOLOGICAL RESEARCH - A.S. Kolbin; N.P. Shabalov; V.A. Lyubimenko (Педиатрическая фармакология, 2007)
In recent years clinical pharmacologists working in the field of pediatrics all across the world scrutinize the application issues of unlicensed medications among children. Based on the example of a group of patients consisting of 449 premature infants and with the aid of the pharma coepidemiological research, the authors showed the usage rate of unlicensed anti infectious medications in neonatology. The analysis embraced the 9 year long period of work of the largest neonatal center in northwest. As a result they uncovered that the anti infectious medications which were prescribed most often were aminoglycoside and cephalosporin antibiotics. The applied medications were referred to the unlicensed in neonatology in 21% of cases, and in 8% of cases they were used off label. Further more, it was noted that there was a general trend towards the considerable increase of application of the banned medications for the analyzed period.Key words: very low birth infants, unlicensed drugs.